Does Social Media Influencer Credibility Drive Purchase Intention? The Mediating Role of Attitude Toward Brand in Social Media Marketing - Ahmad Toriqur Rizqi; Ratih Amelia (Jurnal Mirai Management, 2026)
This study aims to examine the relationship between social media influencer credibility and purchase intention, as well as to investigate the mediating role of attitude toward brand in this relationship. This research employs a quantitative approach using a survey method. Data were collected from 200 respondents who are familiar with Mykonos perfume through social media influencers. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS software to evaluate both measurement and structural models. The results indicate that social media influencer credibility does not have a direct significant effect on purchase intention. However, it has a positive and significant effect on attitude toward brand, which in turn significantly influences purchase intention. Furthermore, the findings confirm that attitude toward brand fully mediates the relationship between social media influencer credibility and purchase intention. This study contributes to the influencer marketing literature by integrating Source Credibility Theory and Theory of Reasoned Action into a single framework and by highlighting the critical role of attitude toward brand as a full mediator in explaining the influence of influencer credibility on purchase intention. Keywords: Social media influencer credibility; Brand attitude; Purchase intention; Digital marketing; Local Perfume.